International Student Engagement in Continuous Learning Participation: An Integrated Approach with Entrepreneurial Activities - Mahadianto, Moh Yudi; S., Nelia Fariani; Aung, Saw Htin Lin (KnE Social Sciences, 2025)
This research examines international students’ involvement in continuous learning participation using data obtained from the integrated method and analyzed through a mixed methods approach and means-ends chains. Cluster analysis was conducted to identify mixed method types. An initial qualitative survey with 30 respondents generated questionnaire items, and a quantitative survey to compile a value map was conducted targeting 100 respondents. Cluster analysis identified bicultural acceptance, heritage culture maintenance, and bicultural marginalization as different types that differentiate the level of acculturation among international students. The results of the three types of acculturations show that significant items and strong associations between attribute-consequence and consequence-value at each level reflect the inner thoughts and intrinsic values of international students. These strong associations provide a value map, differentiated by acculturation type. The findings suggest that the availability of integrated services is necessary to better meet the specific interests of international students at different stages of acculturation. Given that the mobility of international students has increased substantially, professionals and relevant entrepreneurial organizations should understand that international students’ sustained engagement in entrepreneurial activities can only be achieved if attention is paid to the cultural context.